Perilunate Injury with Concomitant Short Radiolunate Ligament Disruption: Prevalence and Surgical Outcomes—"An Unusual Perilunate Injury Variant” - Sgromolo, Nicole M.; Mullikin, Ian A.; Rhee, Peter C. (Journal of Wrist Surgery, 2020)
Background In the classic description of perilunate injuries, the short radiolunate ligament (SRL) remains intact.Objective This study was aimed to determine the occurrence of SRL disruptions with perilunate injuries and review the clinical and radiographic outcomes after surgical management.Patients and Methods A retrospective review was conducted for patients who sustained a perilunate injury and a concomitant disruption of the SRL at a single–level-1 trauma center between January 2013 and January 2017. Patients with the combined injury pattern were compared with those with perilunate injury alone without SRL injury during the study period. Outcome measures included pain scores (visual analogue score), wrist and forearm range of motion, patient's return to their former occupation, and multiple radiographic parameters.Results Twenty-seven patients were treated operatively for a perilunate injury. Eight of these patients (30%) were found to have associated disruption of the SRL. When compared with patients with perilunate injury alone, these patients had a lower rate of return to work (57% [4 of 7] vs. 92% [12 of 13]), a significantly longer mean length of time to return to work (5.9 vs. 3.8 months), and a higher rate of associated upper extremity injury (75% [3 of 8] vs. 16% [3 of 19].Conclusion Combined SRL disruption and perilunate dislocation or fracture dislocation represent a high-energy variant from the classic description of a perilunate injury. A heightened awareness for this combined injury pattern should be maintained when treating patients with perilunate injuries.Level of Evidence This is a Level III, prognostic study.
Keywords: perilunate injury; radiocarpal dislocation; perilunate dislocation; transscaphoid perilunate fracture dislocation; short radiolunate ligament